The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13229-018-0191-y
|View full text |Cite
|
Sign up to set email alerts
|

Significant transcriptional changes in 15q duplication but not Angelman syndrome deletion stem cell-derived neurons

Abstract: BackgroundThe inability to analyze gene expression in living neurons from Angelman (AS) and Duplication 15q (Dup15q) syndrome subjects has limited our understanding of these disorders at the molecular level.MethodHere, we use dental pulp stem cells (DPSC) from AS deletion, 15q Duplication, and neurotypical control subjects for whole transcriptome analysis. We identified 20 genes unique to AS neurons, 120 genes unique to 15q duplication, and 3 shared transcripts that were differentially expressed in DPSC neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…Therefore, the assessment of the sympathetic nerve activity may be useful for the early diagnosis of ASD. It has been reported that the expression of the HAND2 gene, which encodes a transcription factor and is required for sympathetic neuron survival 35 , was decreased in neurons derived from human Chr. 15q11.2-q13.1 duplicated ASD stem cells 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the assessment of the sympathetic nerve activity may be useful for the early diagnosis of ASD. It has been reported that the expression of the HAND2 gene, which encodes a transcription factor and is required for sympathetic neuron survival 35 , was decreased in neurons derived from human Chr. 15q11.2-q13.1 duplicated ASD stem cells 35 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the expression of the HAND2 gene, which encodes a transcription factor and is required for sympathetic neuron survival 35 , was decreased in neurons derived from human Chr. 15q11.2-q13.1 duplicated ASD stem cells 35 . Hence, our results of lower activities of the sympathetic nervous system in the fetal stage of the ASD model mice could explain the impaired sympathetic survival and/or development detected in ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a transcriptional regulation mechanism appears unlikely as in flies expression levels of Mef2 were unaltered upon Ube3a knockdown and vice versa, and as in a human cell line UBE3A knockdown did not change MEF2C expression levels. Additionally, stem cell-derived neurons modelling Angelman syndrome, did not show significant transcriptional changes of other genes (compared to 15q duplication neurons) 52 . As the most likely hypothesis, we suggest that UBE3A might regulate MEF2C activity and levels by ubiquitination, leading to subsequent degradation in the proteasome.…”
Section: Genetic Interaction Between Ube3a and Mef2mentioning
confidence: 88%
“…PSC models of neurodevelopmental disorders caused by mutations in single genes have been established and include those for Rett syndrome (MECP2 [MIM: 300005]), [304][305][306][307][308] tuberous sclerosis (TSC1 [MIM: 605284]), [309][310][311] and FXS. [312][313][314][315][316] More complex genetic disorders have benefitted from the ability to retain the chromosomal defect in hiPSCs for disorders that result in deletions or duplications of chromosomal regions, such as 15q11.2 microdeletion syndrome (MIM: 615656), 317 Prader-Willi syndrome (MIM: 608636), 318,319 and DS. [320][321][322][323][324] Some phenotypes in neural cells derived from these cells link to disease symptomology, whereas other phenotypes do not, and there is variability in the phenotypes in different reports.…”
Section: Human Stem Cells For Modeling Neurodevelopmental Disordersmentioning
confidence: 99%